УКРАИНЦЫ РЕСПУБЛИКИ МОЛДОВА В БИБЛИОГРАФИЧЕСКИХ ИССЛЕДОВАНИЯХ - БАРБЭ, заведующая Филиалом им. Л. Украинки, Людмила (BIBLIOPOLIS, 2020)
The article is about the publication of Lesia Ukrainka Branch, structured on the principle of personalia, with elements of bibliography. The publication will include a biography of Ukrainian personalities, which live in the Republic of Moldova. The content will reflect the scientific achievements of the Ukrainians from the Republic of Moldova, theirs educational, literary activities, the contribution of the Ukrainians in development of the theatre and music in the Republic of Moldova. The reference book will include materials about scientists, educators, painters, composers, writers and artists who have left their trace on the development of the Republic of Moldova, who wrote their pages in the cultural heritage.